Impact of postsurgical opioid use and ileus on economic outcomes in gastrointestinal surgeries. (10th February 2015) - Gan, Tong J.; Robinson, Scott B.; Oderda, Gary M.; Scranton, Richard; Pepin, Jodie; Ramamoorthy, Sonia
Abstract: Objectives: To assess the incidence and economic impact of postoperative ileus (POI) following laparotomy (open) and laparoscopic procedures for colectomies and cholecystectomies in patients receiving postoperative pain management with opioids. Methods: Using the Premier research database, we retrospectively identified adult inpatients discharged between 2008 and 2010 receiving postsurgical opioids following laparotomy and laparoscopic colectomy and cholecystectomy. POI was identified through ICD-9 diagnosis codes and postsurgical morphine equivalent dose (MED) determined. Results: A total of 138, 068 patients met criteria, and 10.3% had an ileus. Ileus occurred more frequently in colectomy than cholecystectomy and more often when performed by laparotomy. Ileus patients receiving opioids had an increased length of stay (LOS) ranging from 4.8 to 5.7 days, total cost from $9945 to $13, 055 and 30 day all-cause readmission rate of 2.3 to 5.3% higher compared to patients without ileus. Patients with ileus received significantly greater MED than those without (median: 285 vs. 95 mg, p  < 0.0001) and were twice as likely to have POI. MED above the median in ileus patients was associated with an increase in LOS (3.8 to 7.1 days), total cost ($8458 to $19, 562), and readmission in laparoscopic surgeries (4.8 to 5.2%). Readmission rates were similar in ileus patients undergoing open procedures regardless of MED. Conclusions: Use of opioids in patients who develop ileus following abdominal surgeries is associated with prolonged hospitalization, greater costs, and increased readmissions. Furthermore, higher doses of opioids are associated with higher incidence of POI. Limitations are related to the retrospective design and the use of administrative data (including reliance on ICD-9 coding). Yet POI may not be coded and therefore underestimated in our study. Assessment of pre-existing disease and preoperative pain management was not assessed. Despite these limitations, strategies to reduce opioid consumption may improve healthcare outcomes and reduce the associated economic impact.